AKUNTANSI SYARIAH DALAM MANAJEMEN KEUANGAN MASJID DI INDONESIA - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to determine the accounting for mosque management on the basis of sharia financial management. This research method is a qualitative type of literature study. Sharia finance has an important role in managing mosque finances. By implementing sharia financial principles, mosques can ensure that the funds they manage are in accordance with Islamic values, avoiding usury and practices that are not in accordance with sharia. Mosque financial management based on sharia financial management ensures transparency, accountability and fairness in the use of mosque funds. Sharia management principles, such as independent oversight and sustainable financial planning, can help achieve this goal. The development of sharia investment-based mosque funds can provide long-term benefits for mosques